Mathematical and Molecular Topology - JÄNTSCHI, Lorentz; Tomescu, Mihaela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, "Mathematical and Molecular Topology" welcomed papers from a broad interdisciplinary area, since topology is concerned with the properties of objects that are preserved under continuous deformations, such as stretching, twisting, crumpling and bending. One of the oldest problems in topology is The Seven Bridges of Königsberg. Topology naturally finds application in all fields of engineering, physical sciences, life sciences, social sciences, medicine, business and even arts. The motivating insight behind topology is that some geometric problems depend not on the exact shape of the objects involved, but rather on the way they are put together. Circa 1750, Euler stated the polyhedron formula, V − E + F = 2 (where V, E, and F respectively indicate the number of vertices, edges, and faces of the polyhedron), which may be regarded as the first theorem, signaling the birth of topology. Subjects included in topology are graph theory and algebraic topology.